Post-fire restoration of pine forests in the Badary area, Tunkinskiy National Park, Russia - Atutova, Zhanna V. (Nature Conservation Research: Заповедная наука, 2023)
A morphological variety of pyrogenic transformations characterises burnt areas of the Badary area of the Tunkinskiy National Park (Russia), from heavily damaged areas with a partially remained forest stand to bare spaces of tens of square metres. This enabled us to study the dynamics of the post-fire reproduction of Pinus sylvestris (hereinafter – pine) forests in areas with various environmental conditions. The main goal of our study was to determine the nature of the pyrogenic transformation of ecosystems and to evaluate the success of the forest reproduction. The studies were based on the geobotanical monitoring in two burnt-out areas, differing in the degree and area of wildfire damage due to a creeping fire in 2010. Between 2014 and 2020, we considered the multi-temporal specificity of the species composition of the forest stand, shrub layer, and plant communities. The emergence of the first shoots of undergrowth and new growth has been recorded. The projective cover and the dynamics of the species abundance in all forest layers were fixed. The analysis of the natural reforestation dynamics revealed a similarity of the main geobotanical indicators. Pine seedlings dominated in the undergrowth of the study sites, with a small proportion of Betula pendula. The shrub layer consisted of Rosa acicularis. Rhododendron dauricum has been found there only at the late stage of the study. In the herbaceous layer, the largest proportion was represented by meadow species, with a small participation of forest plants. Differences were revealed during the emergence of first seedlings of undergrowth and new growth, as well as in the size of projective cover of species in all forest layers. The first pine seedlings on a heavily burnt-out study plot were recorded a year earlier than on a less transformed plot. Nevertheless, the height increment and the projective cover of the undergrowth were significantly higher on the burnt-out area of a medium damage degree. On the heavily fire-damaged area, we observed pine seedlings planted by the staff of the Tunkinskiy National Park. A satisfactory rate of seedling survival at the initial stage and further deceleration of growth parameters have been noted. The obtained results indicate the reforestation success and, therefore, a favourable forecast of post-fire recovery of light-coniferous forests in the Badary area of the Tunkinskiy National Park.